Sri Lanka : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
Since the last Article IV Consultation, the Sri Lankan economy has advanced on several fronts. However, the economic effects of the two-decade long civil conflict are yet to be overcome, and many challenges remain. Recently, heightened political uncertainty has constrained the government's ability to push ahead with reforms. The financial sector performed well in 2003, but has reacted nervously to recent political developments. The Central Bank of Sri Lanka (CBSL) cut repo rates by 275 basis points over the year.